Hobbing Error and Adjustment of Worm-gear Tooth Surface - Lu Jianwei; Chen Ningxin (Jixie chuandong)
At present,there are two different kinds of worm-gear hobs in domestic: outer diameter increment hob and pitch diameter increment hob.The outer diameter increment hob has been eliminated a long time ago in the most of the developed industrial countries because of its short service life.However,the pitch diameter increment hob needs to set mounting tilt angle and manufacturing center distance that differs from nominal center distance during hobbing.And following the hob reshaping that reduces the hob pitch diameters,the tilt angle and manufacturing center distance have to be re-calculated and adjusted.Any incorrectness of those two settings will cause worm-gear tooth surface error.The calculation equations of tilt angle and manufacturing center distance are introduced,the error of worm-gear tooth surface caused by the above incorrectness machining parameters settings are analyzed.Two calculation examples,one for single head worm-gear and another for multi-starts of worm are given readers to reveal the distribution of the worm gear tooth surface error,the basis for correcting the machining tool parameter error is provided.